Enhancing Student Learning Engagement through Fiqh Teachers’ Instructional Strategies: Evidence from an Islamic Senior High School - Putri, Rizkiah Mutmainnah; Hasirah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Learning engagement is a critical factor influencing students’ academic success, particularly in religious education where active participation is essential for meaningful understanding. However, many students in Islamic secondary education still demonstrate limited participation during classroom learning activities. This study aims to examine the instructional strategies employed by Fiqh teachers to enhance students’ learning engagement at Madrasah Aliyah 5 Batanghari, Jambi, Indonesia. The study employed a qualitative research design using a case study approach. Data were collected through classroom observations, in depth interviews with teachers and students, and document analysis. The findings reveal that Fiqh teachers apply several instructional strategies to promote active learning, including interactive questioning techniques, collaborative learning activities, contextual explanations, and the integration of real-life religious practices in classroom discussions. These strategies were found to significantly encourage student participation, improve classroom interaction, and foster a more engaging learning environment. The study contributes to the growing body of literature on Islamic education by providing empirical insights into effective pedagogical strategies that support student engagement in religious learning contexts. The findings also offer practical implications for teachers and educational institutions in developing more interactive and student centered approaches in Fiqh instruction.